PENGARUH PEMBELAJARAN PROBLEM SOLVING, STAD DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA, BIDANG STUDI EKONOMI - Imam Makhfudi (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2018)
The research purpose is to know: (1) There is differences in economic learning results using Problem Solving, STAD in grade XII students SMAN I Lamongan, SMAN I kembangbahu. (2) The difference of economic learning outcomes between high motivation students and low motivation (3) There is interaction between the use of learning model and motivation to learn on the economic learning outcomes. Data were collected using a multiple-choice test and a rating scale motivation questionnaire. Data were analyzed using inferential statistics of anova two factors. The average score of student learning outcomes with Problem Solving, 83.84, STAD type 76.56, and average score of student learning outcomes highly motivated 83.07, low motivation 76.32. Hypothesis test Anava (1) F count for 35.512, sig. 0.000 <0.05, There is effect of learning outcomes students who were taught by Problem Solving and STAD type. (2) F count for 25.196, sig. 0.000 <0.05. There is effect of learning outcomes between students who are highly motivated and low motivated. (3) obtained F count of 9.164, sig. 0.003 <0.05, it can be concluded there is interaction between learning model and motivation to result learn. So the interaction between motivation and learning model influence together to increase student learning outcomes.